Pengaruh Media Sosial dan Teman Sebaya terhadap Perilaku Konsumtif Mahasiswa: Studi Kasus Mahasiswa Febi UINSU - Aqila Tamima; Mhd. Arifta Pulung Tumangger; Dini Lestari (JURNAL EDUKASI NONFORMAL, 2023)
The aims of this study were: 1) to determine the effect of social media on student consumptive behavior; 2) to determine the influence of peers on student consumptive behavior; 3) to determine the effect of social media and peers on the consumptive behavior of Febi Uinsu students. This type of correlational research with a sample of 100. The data collection technique uses a questionnaire. The data analysis technique uses multiple linear regression. The results of the study show 1) there is an influence of social media on student consumptive behavior; 2) there is influence of peer association on student consumptive behavior and 3) there is influence of social media and peers on student consumptive behavior.